Megaprojects : lessons on risk and project management from the Big Dig - Greiman, Virginia (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Project management lessons learned on the Big Dig, America's biggest megaproject, by a core member responsible for its daily operations In Megaproject Management, a central member of the Big Dig team reveals the numerous risks, challenges, and accomplishments of the most complex urban infrastructure project in the history of the United States. Drawing on personal experience and interviews with project engineers, executive oversight commission officials, and core managers, the author, a former deputy counsel and risk manager for the Big Dig, develops new insights as she describes the realities of day, to, day management of the project from a project manager's perspective. The book incorporates both theory and practice and is therefore highly recommended to policymakers, academics, and project management practitioners. Focusing on lessons learned, this insightful coursebook presents the Big Dig as a massive case study in the management of risk, cost, and schedule, particularly the interrelation of technical, legal, political, and social factors. It provides an analysis of the difficulties in managing megaprojects during each phase and over the life span of the project, while delivering useful lessons on why projects go wrong and what can be done to prevent project failure. It also offers new ideas to enhance project management performance and innovation in our global society. This unique guide: -Defines megaproject characteristics and frameworks -Reviews the Big Dig's history, stakeholders, and governance -Examines the project's management scope, scheduling, and cost management'including project delays and cost overruns -Analyzes the Big Dig's risk management and quality management -Reveals how to build a sustainable project through integration and change introduction.
Introduction to megaprojects and the Big Dig -- History and financing of the Big Dig -- Stakeholders -- Governance -- Megaproject scope management -- Schedule -- Cost history -- Cost management -- Megaprojects and megarisk -- Quality management -- Building a sustainable project through integration and change -- Leadership -- Appendix.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Central Artery/Third Harbor Tunnel Project (Mass.) -- Case studies; Central Artery/Third Harbor Tunnel Project (Mass.); Central Artery/Third Harbor Tunnel Project (Mass.); Tunnels -- Massachusetts -- Boston -- Design and construction -- Case studies; Public works -- Massachusetts -- Boston -- Management -- Case studies; Project management -- Case studies; Risk management -- Case studies; BUSINESS & ECONOMICS -- Project Management; TECHNOLOGY & ENGINEERING -- Project Management; Project management; Public works -- Management; Risk management; Tunnels -- Design and construction; Massachusetts -- Boston; Electronic books; Case studies; Electronic books